Evaluation of Laboratory Methods for the Diagnosis of Entamoeba histolytica Among Children in Port Harcourt, Rivers State - Isomah Chiladi; Christian Mbata U; Priya Huoma; Isomah Abiye Chiladi (Research Synergy Foundation, 2022)
The prevalence of Entamoeba histolytica using different methods in detecting the causative pathogens causing amoebic dysentery among children in Rivers State was carried out using standard laboratory procedures. This research was carried out in some selected health establishments in Port Harcourt City, the capital of Rivers State, Nigeria. The aim of the study was to evaluate the prevalence of E. histolytica among children in Port Harcourt, Rivers State. The study which involved about one thousand stool samples were collected from consented subjects in Rivers State hospitals, of which 533 fecal specimens from male and 467 from female children were collected. Stool sample examined using the three diagnostic methods which were microscopic methods using normal saline and lugol’s iodine, formol-ether sedimentation technique and Entamoeba culture methods. The results showed that, out of the 1000 stool samples examined, 54 (5.4%) were positive for cyst and or trophozoites of E. histolytica when examined by direct saline and lugol’s iodine bright light microscopy. Twenty-one (2.1%) showed presence of E. histolytica when processed by sedimentation method, whereas 87 (8.7%) showed presence of E. histolytica in all the samples processed by culture method. These results implementing 89%, 81% and 95% specificity for microscopy, sedimentation and culture method respectively. Furthermore, culture method, microscopy method and sedimentation method showed sensitivity of 95% 62% and 40% respectively. Data analysis of kappa statistics showed culture method have the highest value of (0.75) followed by microscopy (0.55) and sedimentation (0.33). Finally, culture method which is the most reliable test method could be a very useful tool in the routine assessment as well as surveillance of E. histolytica in a developing country like Nigeria. Therefore, public and personal health hygiene should be taken seriously to avoid and control the infection in Rivers State.